Immunization With a Novel Human Type 5 Adenovirus-Vectored Vaccine Expressing the Premembrane and Envelope Proteins of Zika Virus Provides Consistent and Sterilizing Protection in Multiple Immunocompetent and Immunocompromised Animal Models. (29th March 2018) - Guo, Qiang; Chan, Jasper Fuk-Woo; Poon, Vincent Kwok-Man; Wu, Shipo; Chan, Chris Chung-Sing; Hou, Lihua; Yip, Cyril Chik-Yan; Ren, Changpeng; Cai, Jian-Piao; Zhao, Mengsu; Zhang, Anna Jinxia; Song, Xiaohong; et al.
Abstract : A novel human type 5 adenovirus-vectored vaccine expressing the premembrane and envelope proteins of Zika virus elicits sterilizing immunity in vaccinated mice and protects them from Zika virus infection. Abstract: Background: Zika virus (ZIKV) infection may be associated with severe complications and disseminated via both vector-borne and nonvector-borne routes. Adenovirus-vectored vaccines represent a favorable controlling measure for the ZIKV epidemic because they have been shown to be safe, immunogenic, and rapidly generable for other emerging viral infections. Evaluations of 2 previously reported adenovirus-vectored ZIKV vaccines were performed using nonlethal animal models and/or nonepidemic ZIKV strain. Methods: We constructed 2 novel human adenovirus 5 (Ad5)-vectored vaccines containing the ZIKV premembrane-envelope (Ad5-Sig-prM-Env) and envelope (Ad5-Env) proteins, respectively, and evaluated them in multiple nonlethal and lethal animal models using epidemic ZIKV strains. Results: Both vaccines elicited robust humoral and cellular immune responses in immunocompetent BALB/c mice. Dexamethasone-immunosuppressed mice vaccinated with either vaccine demonstrated robust and durable antibody responses and significantly lower blood and tissue viral loads than controls ( P < .05). Similar findings were also observed in interferon-α/β receptor-deficient A129 mice. In both of these immunocompromised animal models, Ad5-Sig-prM-Env-vaccinated mice had significantly ( P < .05) higher titers of anti-ZIKV-specific neutralizing antibody titers and lower (undetectable) viral loads than Ad5-Env-vaccinated mice. The close correlation between the neutralizing antibody titer and viral load helped to explain the better protective effect of Ad5-Sig-prM-Env than Ad5-Env. Anamnestic response was absent in Ad5-Sig-prM-Env-vaccinated A129 mice. Conclusions: Ad5-Sig-prM-Env provided sterilizing protection against ZIKV infection in mice.